2011
DOI: 10.1002/hipo.20813
|View full text |Cite
|
Sign up to set email alerts
|

Kappa opioid receptor activation blocks progressive neurodegeneration after kainic acid injection

Abstract: We recently demonstrated that endogenous prodynorphin-derived peptides mediate anticonvulsant, antiepileptogenic and neuroprotective effects via kappa opioid receptors (KOP). Here we show acute and delayed neurodegeneration and its pharmacology after local kainic acid injection in prodynorphin knockout and wild-type mice and neuroprotective effect(s) of KOP activation in wild-type mice. Prodynorphin knockout and wild-type mice were injected with kainic acid (3 nmoles in 50 nl saline) into the stratum radiatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 51 publications
0
12
0
2
Order By: Relevance
“…Treatment of mice injected with kainic acid with the κ receptor agonist U‐50488H results in reduced neuronal loss (Schunk et al , ) and reduces hippocampal paroxysmal discharges (this study). However, general κ receptor agonists induce dysphoria in humans (Barber and Gottschlich, ) and aversive effects in mice (Land et al , ).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Treatment of mice injected with kainic acid with the κ receptor agonist U‐50488H results in reduced neuronal loss (Schunk et al , ) and reduces hippocampal paroxysmal discharges (this study). However, general κ receptor agonists induce dysphoria in humans (Barber and Gottschlich, ) and aversive effects in mice (Land et al , ).…”
Section: Discussionmentioning
confidence: 51%
“…Various selective κ receptor agonists applied through different routes yielded time‐dependent and dose‐dependent effects similar to those upon treatment with phenytoin or phenobarbital in models of epilepsy (see Simonato and Romualdi, ). We recently demonstrated that the activation of κ receptors promotes the survival of hippocampal and amygdala neurons subsequent to the acute phase after unilateral injection of kainic acid in mice (Schunk et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype could be entirely rescued by kappa receptor-specific agonist while a delta-specific agonist decreased seizure threshold in both wild-type and knockout mice [141]. Moreover prodynorphin knockout mice showed faster seizure onset and a prolonged time of seizure activity after kainate injection, which was accompanied by an increased extent of neuronal loss in the hippocampus [142]. The involvement of dynorphin in the etiology of epilepsy was also strengthened by a functional polymorphism in the prodynorphin gene promotor associated with temporal lobe epilepsy.…”
Section: Dynorphin and Enkephalinmentioning
confidence: 97%
“…Thus, the net effect would be decreased signaling via the KOR. Partial agonists at the KOR, as opposed to antagonists, could be of special importance in the alcohol dependence field because of evidence showing that withdrawal in alcohol dependent individuals can be characterized by increased seizure probability and that KOR stimulation in the hippocampus protects against the production of certain types of seizures (Loacker et al, 2007; Schunk et al, 2010)…”
Section: Negative Reinforcement In Alcohol-dependent Populationsmentioning
confidence: 99%